1999
DOI: 10.1073/pnas.96.12.6654
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of endogenous ouabain

Abstract: The ouabain-like sodium pump inhibitor in mammals (so-called ''endogenous ouabain'') has been considered a subtle structural isomer of ouabain. Its structural investigation, however, has long been hindered by the paucity of sample material. Our recent purification of endogenous ouabain (3 g) from bovine hypothalamus allowed the measurement of its 1 H-NMR. The obtained spectrum as well as reexamination of past microscale structural studies on endogenous ouabain led us to identify the purified material as ouabai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(59 citation statements)
references
References 30 publications
(6 reference statements)
1
56
0
2
Order By: Relevance
“…Endogenous ouabain is, like other steroid hormones, synthesized and released from the adrenals (21). It is also locally produced in other tissues, such as the hypothalamus (16,18). Its physiological role has not been clarified (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenous ouabain is, like other steroid hormones, synthesized and released from the adrenals (21). It is also locally produced in other tissues, such as the hypothalamus (16,18). Its physiological role has not been clarified (37).…”
Section: Discussionmentioning
confidence: 99%
“…Ouabain derivatives have been used for centuries in the treatment of heart disease. Recent studies demonstrate the presence of endogenous ouabain in mammalian tissues (16)(17)(18). The physiological role of the ouabain͞Na,K-ATPase complex has, despite extensive research, remained controversial.…”
mentioning
confidence: 99%
“…It is the target molecule for cardiac glycosides, such as ouabain, which inhibit the enzyme activity by binding from the extracellular side of the enzyme. Recently, the presence of endogenous ouabain has been demonstrated in mammalians (2)(3)(4), and it is suggested that it may play a role in the pathogenesis of hypertension (5). The interaction between ouabain and Na ϩ ,K ϩ -ATPase appears to be important for understanding the regulation of Na ϩ ,K ϩ -ATPase activity.…”
mentioning
confidence: 99%
“…In addition to the cardiac glycosides of plant origin, the endogenous CTS were recently described as a new class of steroid hormones, endogenously produced in mammalian adrenal glands and central nervous system (3). Endogenous ouabain (EO) has been isolated as a stereoisomer of ouabain and identified as a constituent of human blood, bovine adrenal glands, and hypothalamus (3,4) and circulates in elevated concentrations in the blood of 50% of Caucasians with high blood pressure (5). Bovine adrenal cortical cells in tissue culture release EO in response to norepinephrine, corticotropin, and angiotensin II (6,7).…”
mentioning
confidence: 99%